DASHBOARD VISUALIZATION OF FOOD SECURITY IN INDONESIA: ADDRESSING CHALLENGES OF FOOD DISTRIBUTION AND ACCESS - Valentina, Alessandra; Fianty, Melissa Indah; Mashur, Tsabitah Ramadhani; Laurenzia, Kezia Aprila (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Food, a basic human need, is crucial for survival. Food shortages signal vulnerability to food security in a country. This affects the welfare of the people and the economy of a country. This research explores the challenges of food security in Indonesia, where unequal distribution creates access gaps and affects food management. It presents visualizations highlighting aspects of food security, including limited access in vulnerable areas, and emphasizes the need for government intervention to prevent food crises and stunting. The study underscores the importance of optimizing food utilization through education and community empowerment to drive economic growth. In addition, with Indonesia's high population growth, ensuring sustainable food availability is crucial. The visualization takes the National Food Agency dataset, which includes the scores of each province based on aspects of food security. The data is processed and presented using Tableau, representing various visuals such as bar charts, maps, trend lines, and several other visuals made into a dashboard. The results show that food security in each region, especially vulnerable areas, shows good progress. The visualization results can be used as a reference for the government in developing strategies to prevent food crises by considering these aspects in reducing stunting rates and encouraging the economy in Indonesia.